GENERALIZED METHOD OF DETERMINING THE SURFACE-VOLUME TEMPERATURE OF ELEMENTS OF FRICTION UNITS - Kindrachuk, Myroslav; Volchenko, Dmytro; Andreychikov, Evgen; Burava, Oleksandr; Pryyazhny, Andriy; Nishchuk, Viktor (Problems of Friction and Wear, 2024)
The materials of the article contain questions: thermophysical parameters of friction pairs of braking devices; project calculation and analysis of results; discussion of the results. A generalized method of determining the surface-volume temperature of the friction pairs of braking devices with given design parameters and constant values ​​of the thermophysical properties of their materials is proposed, provided that the friction power corresponds to linear or parabolic laws of change and corresponds to the laws of generating heat flows in friction couplings, which made it possible to establish such. The connection between graphical dependencies for linear and parabolic laws of heat release was carried out through the dimensionless value K as a function of the Fourier criterion (F0), and the dependence of the form K=μ(F0) made it possible to estimate the intensity of cooling of the metal friction element using the Bio criterion (Bi), criterion F0 varied from zero to 1.2, and criterion Bi from zero to 1.0. When determining the surface-volume temperature of the "metal-polymer" pair, it was carried out through the coefficient of distribution of heat flows; while the latter acted on the entire thickness of the metal, and in the polymer overlay only on its surface and subsurface layers. When selecting the material for the metal friction element, the coefficient of thermal saturation was used, which includes the coefficient of thermal conductivity, heat capacity and density of the material, which has a larger value. The generalized method is confirmed by bench data on friction pairs of a belt-pad brake and operational tests of friction pairs of a drum-pad brake, in which the material was steel 35ХНЛ-retinax ФК-16Л.